Enhancing colistin efficacy against Salmonella infections with a quinazoline-based dual therapeutic strategy - Lobertti, Carlos Alberto (2024)
Colistin remains one of the last-resort therapies for combating infections caused by multidrug-resistant (MDR) Enterobacterales, despite its adverse nephro- and neuro-toxic effects. This study elucidates the mechanism of action of a non-antibiotic 4-anilinoquinazoline-based compound that synergistically enhances the effectiveness of colistin against Salmonella enterica. The quinazoline sensitizes Salmonella by deactivating intrinsic, mutational, and transferable resistance mechanisms that enable Salmonella to counteract the antibiotic impact colistin, together with an induced disruption to the electrochemical balance of the bacterial membrane. The attenuation of colistin resistance via the combined treatment approach also proves efficacious against E. coli, Klebsiella, and Acinetobacter strains. The dual therapy reduces the mortality of Galleria mellonella larvae undergoing a systemic Salmonella infection when compared to individual drug treatments. Overall, our findings unveil the potential of the quinazoline-colistin combined therapy as an innovative strategy against MDR bacteria.